2015
DOI: 10.1007/s12223-015-0441-8
|View full text |Cite
|
Sign up to set email alerts
|

The microcyclic conidial stage of Coniochaeta pulveracea and its effect on selected biological interactions

Abstract: Coniochaeta pulveracea is a dimorphic lignicolous fungus that has mostly been isolated from decaying wood. However, relatively little work was conducted on the conditions for the dimorphic switch or the biological interactions of the fungus in its yeast-like microcyclic growth phase. Therefore, in this study, the microcyclic conidiation of C. pulveracea strains and representatives of the closely related species, Coniochaeta boothii and Coniochaeta subcorticalis, was studied under different environmental condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The researches on the mechanism of microcycle conidiation is still scarce. Recently, studies about microcycle conidiation mostly focus on the phenotypic observation in different fungi (Souza-Paccola et al, 2015; van Heerden et al, 2016; Rosli et al, 2018). In the preliminary work in our lab, we found that normal conidiation and microcycle conidiation are involved in lipid metabolism, sugar chain biosynthesis, and metabolism and translation (Wang Z. et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The researches on the mechanism of microcycle conidiation is still scarce. Recently, studies about microcycle conidiation mostly focus on the phenotypic observation in different fungi (Souza-Paccola et al, 2015; van Heerden et al, 2016; Rosli et al, 2018). In the preliminary work in our lab, we found that normal conidiation and microcycle conidiation are involved in lipid metabolism, sugar chain biosynthesis, and metabolism and translation (Wang Z. et al, 2016).…”
Section: Discussionmentioning
confidence: 99%